Fossil bats of the Late Pleistocene from Huautla System Caves (Oaxaca, Mexico) and the importance of carpus bones to fossil identification - Gaudioso, Pablo Javier (2025)
The carpal bones, which show a notorious specialisation towards flight are poorly studied. These bones have only been the subject of study in 0.2% of all extant bat species. The use of bones from the carpal region has not been extensively investigated in palaeontology, mainly due to the scarcity of osteological studies and the fact that they are rarely collected during excavations. Therefore, we document the identification of a Pleistocene bat using the: scaphocentralunates. The material was collected from sediments associated with the extinct sloth Meizonyx salvadorensis, found in the caves of Sistema Huautla, Oaxaca, Mexico. A combination of qualitative and quantitative morphological characteristics made it possible to identify the scaphocentralunar bones at the generic level, which were subsequently determined to belong to the bat species Sturnira sp. This finding demonstrates that the carpal bones in bats exhibit distinctive diagnostic characteristics for the identification of fossil material. The discovery represents the second record for the genus for the Pleistocene of Mexico and the seventh in the Americas continent. In addition, the significance of collecting sediments associated with megafauna to obtain a more comprehensive understanding of past diversity is underscored.